The role of husbands in maternal health and safe childbirth in rural Nepal: a qualitative study - Lewis, Sarah (BMC Pregnancy Childbirth, 2015)
BACKGROUND: The role of husbands in maternal health is often overlooked by health programmes in developing countries and is an under-researched area of study globally. This study examines the role of husbands in maternity care and safe childbirth, their perceptions of the needs of women and children, the factors which influence or discourage their participation, and how women feel about male involvement around childbirth. It also identifies considerations that should be taken into account in the development of health education for husbands. METHODS: This qualitative study was conducted in four rural hill villages in the Gorkha district of Nepal. Semi-structured, in-depth interviews were conducted with husbands (n = 17), wives (n = 15), mothers-in-law (n = 3), and health workers (n = 7) in Nepali through a translator. Interviews were transcribed and analysed using axial coding. RESULTS: We found that, in rural Nepal, male involvement in maternal health and safe childbirth is complex and related to gradual and evolving changes in attitudes taking place. Traditional beliefs are upheld which influence male involvement, including the central role of women in the domain of pregnancy and childbirth that cannot be ignored. That said, husbands do have a role to play in maternity care. For example, they may be the only person available when a woman goes into labour. Considerable interest for the involvement of husbands was also expressed by both expectant mothers and fathers. However, it is important to recognise that the husbands’ role is shaped by many factors, including their availability, cultural beliefs, and traditions. CONCLUSIONS: This study shows that, although complex, expectant fathers do have an important role in maternal health and safe childbirth. Male involvement needs to be recognised and addressed in health education due to the potential benefits it may bring to both maternal and child health outcomes. This has important implications for health policy and practice, as there is a need for health systems and maternal health interventions to adapt in order to ensure the appropriate and effective inclusion of expectant fathers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12884-015-0599-8) contains supplementary material, which is available to authorized users.